2019
DOI: 10.3390/ijms20205048
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Cucumber BPC Transcription Factors and Their Responses to Abiotic Stresses and Exogenous Phytohormones

Abstract: BASIC PENTACYSTEINE (BPC) is a small transcription factor family that functions in diverse growth and development processes in plants. However, the roles of BPCs in plants, especially cucumber (Cucumis sativus L.), in response to abiotic stress and exogenous phytohormones are still unclear. Here, we identified four BPC genes in the cucumber genome, and classified them into two groups according to phylogenetic analysis. We also investigated the gene structures and detected five conserved motifs in these CsBPCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The difference between these groups demonstrates that these proteins underwent great genetic variation after divergence, probably due to environmental influences, and that some gene fragments might have been lost during the evolutionary process [ 26 ]. The analysis of gene structure and motif suggested that the S1fa genes shared a similar exon–intron and motif structure, indicating there is a closer evolutionary relationship among the members in the same group but a functionally diversified relationship among the other group members [ 27 , 28 , 29 , 30 ]. The structure and motif analysis of Chinese cabbage S1fa genes showed a similar structure, which has three common motifs ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between these groups demonstrates that these proteins underwent great genetic variation after divergence, probably due to environmental influences, and that some gene fragments might have been lost during the evolutionary process [ 26 ]. The analysis of gene structure and motif suggested that the S1fa genes shared a similar exon–intron and motif structure, indicating there is a closer evolutionary relationship among the members in the same group but a functionally diversified relationship among the other group members [ 27 , 28 , 29 , 30 ]. The structure and motif analysis of Chinese cabbage S1fa genes showed a similar structure, which has three common motifs ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical parameters including protein isoelectric point (pl), molecular weight (kDa) and length were calculated using the tools on the ExPASy server ( (accessed on 22 March 2022)). The chromosomal locations and strand directions were obtained from the BRAD database ( (accessed on 22 March 2022)), and the subcellular location of each protein was investigated using CELLO 2.5 ( (accessed on 22 March 2022)) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several gene families related to abiotic stress resistance have been identified and investigated. These include WAX [90], YUCCA (YUC) [91], stachyose synthase (STS) [92], plant glycine-rich RNA-binding protein (GR-RBP) [93], basic pentacysteine (BPC) [94], WRKY [95], trehalose-6-phosphate synthase (TPS) [96], tubby-like protein (TLP) [97], and zinc finger-homeodomain (ZF-HD) family genes [98]. In addition to providing a valuable basis for functional research, related studies have analyzed the different stress responses of these genes and the physiological regulatory pathways involved.…”
Section: Functional Genes That Resist Abiotic Stressmentioning
confidence: 99%
“…Many transcription factor gene families (TFs) were studied in the majority of these 21 articles [6,8,9,11,[13][14][15][16][17][18][19][20]23,24]. Various putative stress-related and hormone-responsive cis-acting regulatory elements were identified in the promotor of these TFs.…”
Section: Chromosomal Distribution Patterns Of Genes For Abiotic-stresmentioning
confidence: 99%